Immediate compared with late repair of extracranial branches of the facial nerve: a comparative study. Issue 2 (February 2020) - Kannan, R.Y.; Hills, A.; Shelley, M.J.; Bisase, B.; Kapoor, K.; Norris, P.; Nduka, C.
Abstract: The best outcomes after injury to the facial nerve are seen after immediate direct coaptation, but in practice, this happens infrequently. We ask whether late repair (between 3 weeks and 18 months) is comparable to immediate repair. In this prospective observational study over a two-year period (2016–18), we identified 18 patients (11 male and 7 female, mean (range) age 58 (23–94) years), who had sustained extracranial injuries to the facial nerve. Eight were identified in the acute phase (within 72 hours of injury) and repaired (immediate repair group). Ten presented in the late phase beyond six months (late repair group), and had direct coaptation, neurolysis, nerve transfer, or non-vascularised or vascularised nerve grafts. Patients were followed up clinically with photographic or video analysis every three months using the Sunnybrook facial grading scale and Terzis scores as quantitative tools. In the immediate repair group six patients had direct nerve coaptations, one had a free vascularised nerve graft, and one a fascicular nerve flap. In the late repair group six patients had coaptations, two had nerve transfers, one had neurolysis, and one nerve transfer and a free vascularised nerve graft. The null hypothesis that there was no difference between immediate and late repair of the facial nerve in terms of clinical improvement was accepted. The overall facial grading scale between the two groups showed no significant difference (mean 97 compared with 87; 95% CI: −25.61 to 5.32; p = 0.18). However, the individual volitional facial grading score for the affected division showed that immediate repair fared significantly better than late repair (mean 4.55 compared with 3.14; 95% CI: −2.5 to −0.3; p = 0.027). Supermicrosurgical techniques, together with advanced systems for nerve identification allow for coaptation of the maximum number of injured nerve branches. These factors accounted for a 97% mean return of function after immediate repair and an 87% recovery in the late repair group. While quantitatively, immediate repair is best, the re-establishment of nerve-muscle continuity before degeneration of the motor endplate confers the best possible physiological outcome, and is far superior to any of the techniques used to treat chronic facial paralysis.